Gender congruence and body satisfaction in nonbinary transgender people: A case control study. Issue 2 (3rd July 2019) - Jones, Bethany A.; Pierre Bouman, Walter; Haycraft, Emma; Arcelus, Jon
Abstract: Background: Binary transgender people access gender affirming medical interventions to alleviate gender incongruence and increase body satisfaction. Despite the increase in nonbinary transgender people, this population are less likely to access transgender health services compared to binary transgender people. No research has yet understood why by exploring levels of gender congruence and body satisfaction in nonbinary transgender people. Objective: The aim of this study was to compare levels of gender congruence and body satisfaction in nonbinary transgender people to controls [binary transgender people and cisgender (nontrans) people]. Method: In total, 526 people from a community sample in the UK took part in the study (97 nonbinary, 91 binary, and 338 cisgender identifying people). Participants were asked to complete an online survey about gender congruence and body satisfaction. Results: There were differences in gender congruence and body satisfaction between nonbinary and binary transgender people. On sex-specific parts of the body (i.e., chest, genitalia, and secondary sex characteristics), nonbinary transgender people reported significantly higher levels of gender and body satisfaction compared to binary transgender people. However, there was no difference in congruence and satisfaction with social gender role between the two transgender groups (nonbinary and binary). Cisgender people reported significantly higher levels of gender congruence and body satisfaction compared to transgender people (nonbinary and binary). Conclusions: There are differences in gender congruence and body satisfaction between nonbinary and binary transgender people. Nonbinary individuals may be less likely to access transgender health services due to experiencing less gender incongruence and more body satisfaction compared to binary transgender people. Transgender health services need to be more inclusive of nonbinary transgender people and their support and treatment needs, which may differ from those who identify within the binary gender system.